Total Water Storage in Small Islands Using Multi-satellite Products: The case of Cyprus - Mercan, Hüseyin; Özcan, Orkan; Özcan, Orkan (Springer Science and Business Media LLC, 2018)
The world’s longest international undersea water pipeline has recently been laid from southern Turkey to Northern Cyprus to address the water scarcity problems in the Cyprus Island. When completed, the project will add 19.8 million gallons of water annually for drinking and irrigation. Moreover, it will spur further development in the Turkish area divided from Greek community for four decades. Under such circumstances, satellite remote sensing provides a unique tool to evaluate the water policy for the entire island. The objective of this study is, therefore, to examine the potential of satellite-based remote sensing hydrologic models covering a small-scale Mediterranean island, which is under drought conditions. Satellite-based measurements such as GRACE (total water storage), TRMM (precipitation) and MODIS (evapotranspiration) data over a 1°–1° grid together with related information from global hydrological model, specifically WGHM and GLDAS, were collected for this purpose.